The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/eap.2512
|View full text |Cite
|
Sign up to set email alerts
|

Similar zooplankton responses to low pH and calcium may impair long‐term recovery from acidification

Abstract: Throughout much of the 20th century, unprecedented industrial emissions have led to widespread acidification of regions in North America and Europe and, as lake water pH dropped, aquatic ecosystems have experienced dramatic declines in biodiversity. International emission‐control agreements have led to sweeping increases in lake pH, however acid‐structured zooplankton communities still persist in many lakes. Concomitantly, calcium concentrations have been declining as a legacy of acidification and are approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…However, the lack of biotic responses in those lakes may also be caused by the persistent low pH (average values during the last 5 years of sampling: 5.3 ± 0.2, no significant increases during the study period) and the combination of low calcium and high humic content. Low calcium concentration has been shown to limit the recovery of zooplankton after acidification independently of improvement in pH (Ross & Arnott, 2022) and, when associated with high content of humic matter, it even causes declines in zooplankton biomass (Leach et al, 2019). On the other hand, humic substances can buffer against detrimental effects of aluminum (Besser et al, 2019;Herrmann, 2001;Locke, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lack of biotic responses in those lakes may also be caused by the persistent low pH (average values during the last 5 years of sampling: 5.3 ± 0.2, no significant increases during the study period) and the combination of low calcium and high humic content. Low calcium concentration has been shown to limit the recovery of zooplankton after acidification independently of improvement in pH (Ross & Arnott, 2022) and, when associated with high content of humic matter, it even causes declines in zooplankton biomass (Leach et al, 2019). On the other hand, humic substances can buffer against detrimental effects of aluminum (Besser et al, 2019;Herrmann, 2001;Locke, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Gray and Arnott (2009) showed that zooplankton response to the recovery of surface‐water chemistry could vary from limited recovery of species richness in heavily acidified lakes to full recovery in moderately acidified lakes. The recovery of zooplankton from acidification seems to be more strongly affected by physico‐chemical variables, such as persisting low pH, calcium concentration (Ross & Arnott, 2022), and content of organic matter (Leach et al, 2019), than by recolonization from external sources (Keller et al, 2002). Climate change has also been shown to affect several facets of zooplankton communities, such as species distribution, body size, abundances, diversity, food web interactions, and phenology (Carter & Schindler, 2012; Vadadi‐Fülöp et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshwater acidification is harmful to various aquatic organisms. Climate warming and changes in water chemistry profoundly affect the pond’s pH (Ross and Arnott 2022 ). The rise in atmospheric carbon dioxide lowers the pH in ponds.…”
Section: Physical Chemical and Biological Pressures On Pondsmentioning
confidence: 99%
“…6,7 D. magna required high levels of Ca from the surrounding medium to support regular molting, development, reproduction, and other physiological functions. 8 Within D. magna, Ca was primarily distributed in the exoskeleton in the form of carbonates and phosphates. 9 It was reported that Ca concentration of D. magna increased with the Ca contents in the aqueous environment.…”
Section: ■ Introductionmentioning
confidence: 99%